Rosacea Management: Update on general measures and topical treatment options. (December 2016) - Schaller, M; Schöfer, H; Homey, B; Hofmann, M; Gieler, U; Lehmann, P; Luger, TA; Ruzicka, T; Steinhoff, M
Summary: Although there is presently no cure for rosacea, there are several recommended treatment options available to control many of the symptoms and to prevent them from getting worse. In addition to self‐help measures like avoidance of trigger factors and proper skin care, rosacea management should include topical medications as one of the first‐line choices for patients with erythematous and mild to severe papulopustular rosacea. Since mixed forms of characteristic rosacea symptoms are more common, medical treatment must be symptom‐tailored for each individual case and will often involve a combination therapy. Approved topical agents for the major symptoms of rosacea encompass brimonidine for erythema and ivermectin, metronidazole or azelaic acid for inflammatory lesions, all of which have shown their efficacy in numerous valid, well‐controlled trials. In addition, there are several other, not approved topical treatments which are possible options that require further validation in larger well‐controlled studies.